International and foreign experience of control over the activity of courts (judges) - Shcherbanyuk, Oksana; Ilchyshyn, Nadiya; Stepanova, Tetiana; Posashkov, Alexander (DIXI, 2020)
This article, based on the analysis of scientific views of scholars, summarizes the foreign experience of control over the activity of courts (judges). After summarizing the experience of Germany, it is stated that the legal mechanism of control over judges in this country is characterized not only by the differentiation of the distribution of supervisory powers at the federal and regional levels, but also by the active involvement of executive and legislative bodies. It is established that the existing foreign experience of control and supervision over the work of judges is quite diverse and can be used by domestic legislators when introducing amendments and additions to current legislation. The most positive experience that can be used in Ukraine to improve the control over the activity of judges includes: 1) The need to improve the procedure for selecting judges; 2) extension of the statute of limitations for committing an offense as a ground for disciplinary liability, in order to reduce the risk of judges avoiding its occurrence; 3) introduction of new forms and methods of control in the relevant field; 4) improvement of organizational and legal bases of public involvement in the implementation of control and supervision measures in the area under study.